Proceedings of the 2017 Annual Meeting of the Fetal Alcohol Spectrum Disorders Study Group - Wozniak, Jeffrey R. (Alcohol, 2017)
The 2017 Fetal Alcohol Spectrum Disorders Study Group (FASDSG) meeting was entitled “Prenatal alcohol exposure in the context of multiple factors affecting brain development.” The theme was reflected in the interactions between members of the Teratology Society and the FASDSG this year. The first keynote speaker, Elaine Faustman, Ph.D., was a liaison between the societies and spoke about systems biology and the multiple genetic and environmental influences on development. The second keynote speaker, Rebecca Knickmeyer, Ph.D., discussed population neuroscience and multiple influences on brain development. The conference presented updates from three government agencies and short presentations by junior and senior investigators showcasing late-breaking FASD research. The conference was capped by Dr. John Hannigan, Ph.D., the recipient of the 2017 Henry Rosett award for career-long contributions to the field.